A note on irreducible Heegaard diagrams - Alberto Cavicchioli; Fulvia Spaggiari (International Journal of Mathematics and Mathematical Sciences)
We construct a Heegaard diagram of genus three for the real projective 3-space, which has no waves and pairs of complementary handles. The first example was given by Im and Kim but our diagram has smaller complexity. Furthermore the proof presented here is quite different to that of the quoted authors, and permits also to obtain a simple alternative proof of their result. Examples of irreducible Heegaard diagrams of certain connected sums complete the paper.